Analisis Tingkat Pengetahuan dalam Pemanfaatan Layanan Mobile JKN - Nurhidayah, Nurhidayah; Purba, Quen Kholisa; Sitorus, Rehana Nugraha B.; Gurning, Fitriani Pramita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The mobile JKN application is the latest innovation from BPJS health in improving services to the public, especially in the health sector, which can be accessed through smartphones. However, many people still do not utilize this application. This study aims to determine the utilization of the mobile JKN application and measure its effectiveness in improving public health services. The method of writing this journal involves searching for articles through Google Scholar and PubMed with the keywords